Kasus Lupus Vulgaris yang Didiagnosis Tanpa Biopsi Kulit - Dian Puspitasari; Feilicia Henrica (Journal of Medicine and Health, 2020)
Lupus vulgaris is a variant of cutaneous tuberculosis in a previously sensitized individual that has a high degree of delayed-type hypersensitivity to tuberculin. Absolute criteria for the diagnosis of cutaneous tuberculosis is a positive M. tuberculosis culture on guinea pig or polymerase chain reaction (PCR) examination. We reported a case of lupus vulgaris in a 32 years old female. A diagnosis of lupus vulgaris was made by clinical manifestation, therapeutic trial, interferon-gamma release assay (IGRA) test, and other laboratory tests. The patient presented with an erythematous scaly plaque on the face and left hand. Diascopy test was positive, consistent with the “apple jelly” sign. Regression of lesion was observed after 1 month of therapy with anti-tuberculosis drugs. Culture, PCR, and histopathological examination were not established due to patient’s refusal. The patient was allergic to pyrazinamide and ethambutol, therefore she was initially treated with a daily dose of 450 mg Rifampicin, 300 mg isoniazid (INH), and 500 mg levofloxacin for 2 months and continued with maintenance phase, three times weekly of 450 mg Rifampicin and 450 mg INH until one year. Treatment provided a good result. Keywords: tuberculosis; lupus vulgaris; therapeutic trial